The Influence of Work System, Compensation, and Well-Being on Employee Performance at PT Haleyora Powerindo East Java Branch - Fitri Eka Vayuni; Acep Samsudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of work systems, compensation, and well-being on the performance of office employees at PT Haleyora Powerindo, East Java Branch. This research employs a quantitative approach utilizing SPSS version 31 for analysis. The research sample consists of 35 respondents, determined through a saturated sampling technique. Data were collected via questionnaires developed based on the indicators of each research variable. Data analysis was conducted using validity and reliability tests, classical assumption tests, and multiple linear regression analysis, with hypothesis testing performed through t-tests and F-tests. The results indicate that work systems and well-being have a positive and significant effect on employee performance, whereas compensation does not have a partially significant effect. However, work systems, compensation, and well-being simultaneously exert a significant influence on employee performance. These findings emphasize that the effectiveness of work systems and the fulfillment of employee well-being play a crucial role in enhancing performance. This research provides practical contributions for management in formulating human resource management policies oriented toward improving employee performance. Keywords: Work Systems, Compensation, Well-being, Employee Performance